Recreational Utility Hub (RUH): a modular timber-technology fusion hub to support student healthy campus lifestyles / Muhammad Syafiq Aidil Mohd Shahri ... [et al.] - Mohd Shahri, Muhammad Syafiq Aidil; Zainal Abidin, Mohammad Nazrin; Mohammad Ariff Fong, Nur Namirah; Mohd Anuar, Nur Asma (2024)
The Recreational Utility Hub (RUH) is a cutting-edge facility designed to foster a healthy lifestyle among students. By integrating recreation and technology, the RUH creates a dynamic space that promotes both physical and mental well-being. Its modular structure allows for customization to meet diverse recreational support needs, ensuring optimal utilization. Equipped with essential amenities such as charging stations, refrigeration, and digital health tools, the RUH supports a wide range of outdoor activities. A key feature is its sustainable design, which incorporates solar power and timber construction to minimize environmental impact. To enhance user engagement, the RUH leverages modern advancements from the Fourth Industrial Revolution (4IR), including sensor technology, energy storage solutions, and augmented reality (AR). Aligned with Self-Determination Theory, the hub incorporates gamification elements to boost intrinsic motivation and encourage sustained participation. Located at UiTM Perak Branch, Seri Iskandar, the RUH exemplifies how innovative design can transform campus spaces into thriving hubs for student health and happiness.